ADULT EDUCATION IN DENMARK: MODERN DISCOURSE OF LEGISLATIVE SUPPORT - Ангеліна Роляк (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2023)
Sustainable and rational adult education is now a crucial component of the European education system due to the demands of a modern, innovative workforce that must be highly educated and adaptable. This article provides a comparative examination of adult education contemporary situation in Denmark and Ukraine. The author's research interests are in the sphere of the legal frameworks supporting the structural patterns, guiding principles, financing, and acknowledgement of Danish adult education. For the establishment of adult education policies in Ukraine, the Danish setting is essential because of Denmark's unique experience in developing a democratic adult training system that is a part of lifelong learning. In data collection for this study, the author has analyzed multiple legislative sources in European and Danish educational environments at various time points from 2000 to 2023. The conducted research demonstrates that the legal framework in the modern Danish environment encourages adult education in a way that shapes it into a very effective system. On the other hand, significant legislative, structural, and technological changes are needed for adult education in Ukraine, particularly in light of the ongoing aggressive war. This comparative study will contribute to a better understanding of the educational situation with adults in advanced European countries and will help to justify new approaches to the training of adult citizens in Ukraine.